On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

Sustainable oxidation catalysis supported by light: Fe-poly (heptazine imide) as a heterogeneous single-atom photocatalyst - da Silva, Marcos A.R.; Silva, Ingrid F.; Xue, Qi; Lo, Benedict T.W.; Tarakina, Nadezda V.; Nunes, Barbara N.; Adler, Peter; Sahoo, Sudhir K.; Bahnemann, Detlef W.; López-Salas, Nieves; Savateev, Aleksandr; Ribeiro, Caue; et al. (Applied Catalysis B: Environmental)
Keywords: Process Chemistry and Technology; General Environmental Science; Catalysis

Influence of different ester side groups in polymers on the vapor phase infiltration with trimethyl aluminum - Mai, Lukas; Maniar, Dina; Zysk, Frederik; Schöbel, Judith; Kühne, Thomas; Loos, Katja; Devi, Anjana (Dalton Transactions)
The influence of different polymer side chains on the vapor phase infiltration with TMA is investigated and supported by DFT-calculations.
Keywords: Inorganic Chemistry

A Force Field for Bio-Polymers in Ionic Liquids (BILFF) – Part 1: [EMIm][OAc] / Water Mixtures - Roos, E.; Brehm, Martin (Phys. Chem. Chem. Phys.)

Optimized Atomic Partial Charges and Radii Defined by Radical Voronoi Tessellation of Bulk Phase Simulations - Brehm, Martin; Thomas, M. (Molecules)

Unraveling Local Structure of Molten Salts via X-Ray Scattering, Raman Spectroscopy, and ab initio Molecular Dynamics - Roy, S.; Brehm, Martin; Sharma, S.; Wu, F.; Maltsev, D.; Halstenberg, P.; Gallington, L.; Mahurin, S.; Dai, S.; Ivanov, A.; Margulis, C.; Bryantsev, V. (J. Phys. Chem. B)

Liquid Structure and Dynamics in the Choline Acetate:Urea 1:2 Deep Eutectic Solvent - Triolo, A.; Pietro, M. E. Di; Mele, A.; Celso, F. Lo; Brehm, Martin; Lisio, V. Di; Martinelli, A.; Chater, P.; Russina, O. (J. Chem. Phys.)

Switching Between Proton Vacancy and Excess Proton Transfer Pathways in the Reaction Between 7-Hydroxyquinoline and Formate - Codescu, M.-A.; Weiß, M.; Brehm, Martin; Kornilov, O.; Sebastiani, D.; Nibbering, E. T. J. (J. Phys. Chem. A)

Efficient EOM-CC-Based Protocol for the Calculation of Electron Affinity of Solvated Nucleobases: Uracil as a Case Study - Mukherjee, M.; Tripathi, D.; Brehm, Martin; Riplinger, C.; Dutta, A. K. (J. Chem. Theory Comput.)

Liquid Structure of a Choline Chloride-Water Natural Deep Eutectic Solvent: A Molecular Dynamics Characterization - Triolo, A.; Celso, F. Lo; Brehm, Martin; Lisio, V. Di; Russina, O. (J. Mol. Liq.)

Evaluating the Design Space for Offloading 3D FFT Calculations to an FPGA for High-Performance Computing - Ramaswami, Arjun; Kenter, Tobias; Kühne, Thomas; Plessl, Christian (Applied Reconfigurable Computing. Architectures, Tools, and Applications)

“On-The-Fly” Calculation of the Vibrational Sum-Frequency Generation Spectrum at the Air-Water Interface - Ojha, Deepak; Kühne, Thomas D. (Molecules)
In the present work, we provide an electronic structure based method for the “on-the-fly” determination of vibrational sum frequency generation (v-SFG) spectra. The predictive power of this scheme is demonstrated at the air-water interface. While the instantaneous fluctuations in dipole moment are obtained using the maximally localized Wannier functions, the fluctuations in polarizability are approximated to be proportional to the second moment of Wannier functions. The spectrum henceforth obtained captures the signatures of hydrogen bond stretching, bending, as well as low-frequency librational modes.

Disordered crystals from first principles II: Transport coefficients - Kühne, Thomas; Heske, Julian Joachim; Prodan, Emil (Annals of Physics)
This is the second part of a project on the foundations of first-principle calculations of the electron transport in crystals at finite temperatures, aiming at a predictive first-principles platform that combines ab-initio molecular dynamics (AIMD) and a finite-temperature Kubo-formula with dissipation for thermally disordered crystalline phases. The latter are encoded in an ergodic dynamical system (Ω,G,dP), where Ω is the configuration space of the atomic degrees of freedom, G is the space group acting on Ω and dP is the ergodic Gibbs measure relative to the G-action. We first demonstrate how to pass from the continuum Kohn–Sham theory to a discrete atomic-orbitals based formalism without breaking the covariance of the physical observables w.r.t. (Ω,G,dP). Then we show how to implement the Kubo-formula, investigate its self-averaging property and derive an optimal finite-volume approximation for it. We also describe a numerical innovation that made possible AIMD simulations with longer orbits and elaborate on the details of our simulations. Lastly, we present numerical results on the transport coefficients of crystal silicon at different temperatures.

Insight from energy decomposition analysis on a hydrogen-bond-mediated mechanism for on-water catalysis - Salem, M. Alaraby; Kühne, Thomas D. (Molecular Physics)

Correlating facet orientation, defect-level density and dipole layer formation at the surface of polycrystalline CuInSe2 thin films - Elizabeth, Amala; Conradi, Hauke; K. Sahoo, Sudhir; Kodalle, Tim; A. Kaufmann, Christian; Kühne, Thomas; Mirhosseini, Hossein; Abou-Ras, Daniel; Mönig, Harry (Acta Materialia)
Individual grains of chalcopyrite solar cell absorbers can facet in different crystallographic directions at their surfaces. To gain a deeper understanding of the junction formation in these devices, we correlate variations in the surface facet orientation with the defect electronic properties. We use a combined analytical approach based on scanning tunneling spectroscopy (STS), scanning electron microscopy, and electron back scatter diffraction (EBSD), where we perform these experiments on identical surface areas as small as 2 × 2 µm2 with a lateral resolution well below 50 nm. The topography of the absorber surfaces indicates two main morphological features: micro-faceted, long basalt-like columns and their short nano-faceted terminations. Our STS results reveal that the long columns exhibit spectral signatures typical for the presence of pronounced oxidation-induced surface dipoles in conjunction with an increased density of electronic defect levels. In contrast, the nano-faceted terminations of the basalt-like columns are largely passivated in terms of electronic defect levels within the band gap region. Corresponding crystallographic data based on EBSD experiments show that the surface of the basalt-like columns can be assigned to intrinsically polar facet orientations, while the passivated terminations are assigned to non-polar planes. Ab-initio calculations suggest that the polar surfaces are more prone to oxidation and resulting O-induced defects, in comparison to non-polar planes. Our results emphasize the correlation between morphology, surface facet orientations and surface electronic properties. Furthermore, this work aids in gaining a fundamental understanding of oxidation induced lateral inhomogeneities in view of the p-n junction formation in chalcopyrite thin-film solar cells.
Keywords: Chalcopyrite absorber; Scanning tunneling spectroscopy; Electron backscatter diffraction; Density functional theory; Surface dipole

Electrochemical N2 Reduction to Ammonia Using Single Au/Fe Atoms Supported on Nitrogen-Doped Porous Carbon - Sahoo, Sudhir K.; Heske, Julian Joachim; Antonietti, Markus; Qin, Qing; Oschatz, Martin; Kühne, Thomas (ACS Applied Energy Materials)
The electrochemical nitrogen reduction reaction (NRR) to ammonia (NH3) is a promising alternative route for an NH3 synthesis at ambient conditions to the conventional high temperature and pressure Haber--Bosch process without the need for hydrogen gas. Single metal ions or atoms are attractive candidates for the catalytic activation of non-reactive nitrogen (N2), and for future targeted improvement of NRR catalysts, it is of utmost importance to get detailed insights into structure-performance relationships and mechanisms of N2 activation in such structures. Here, we report density functional theory studies on the NRR catalyzed by single Au and Fe atoms supported in graphitic C2N materials. Our results show that the metal atoms present in the structure of C2N are the reactive sites, which catalyze the aforesaid reaction by strong adsorption and activation of N2. We further demonstrate that a lower onset electrode potential is required for Fe--C2N than for Au--C2N. Thus, Fe--C2N is theoretically predicted to be a potentially better NRR catalyst at ambient conditions than Au--C2N owing to the larger adsorption energy of N2 molecules. Furthermore, we have experimentally shown that single sites of Au and Fe supported on nitrogen-doped porous carbon are indeed active NRR catalysts. However, in contrast to our theoretical results, the Au-based catalyst performed slightly better with a Faradaic efficiency (FE) of 10.1{%} than the Fe-based catalyst with an FE of 8.4{%} at −0.2 V vs. RHE. The DFT calculations suggest that this difference is due to the competitive hydrogen evolution reaction and higher desorption energy of ammonia.

Modulation of nearly free electron states in hydroxyl-functionalized MXenes: a first-principles study - Zhou, Jiaqi; Khazaei, Mohammad; Ranjbar, Ahmad; Wang, Vei; Kühne, Thomas D.; Ohno, Kaoru; Kawazoe, Yoshiyuki; Liang, Yunye (J. Mater. Chem. C)

On the Possibility of Helium Adsorption in Nitrogen Doped Graphitic Materials - Kumar Sahoo, Sudhir; Heske, Julian Joachim; Azadi, Sam; Zhang, Zhenzhe; V Tarakina, Nadezda; Oschatz, Martin; Z. Khaliullin, Rustam; Antonietti, Markus; Kühne, Thomas (Scientific Reports)

Energy transfer within the hydrogen bonding network of water following resonant terahertz excitation - Elgabarty, Hossam; Kampfrath, Tobias; Bonthuis, Douwe Jan; Balos, Vasileios; Kaliannan, Naveen Kumar; Loche, Philip; Netz, Roland R.; Wolf, Martin; K{\, Thomas D.; Sajadi, Mohsen (Science Advances)

CP2K: An electronic structure and molecular dynamics software package - Quickstep: Efficient and accurate electronic structure calculations - Kühne, Thomas D.; Iannuzzi, Marcella; Del Ben, Mauro; Rybkin, Vladimir V.; Seewald, Patrick; Stein, Frederick; Laino, Teodoro; Khaliullin, Rustam Z.; Schütt, Ole; Schiffmann, Florian; al., et (The Journal of Chemical Physics)

Oxidation/reduction cycles and their reversible effect on the dipole formation at CuInSe2 surfaces - Elizabeth, Amala; Sahoo, Sudhir K.; Lockhorn, David; Timmer, Alexander; Aghdassi, Nabi; Zacharias, Helmut; Kühne, Thomas; Siebentritt, Susanne; Mirhosseini, Hossein; Mönig, Harry (Phys. Rev. Materials)
The defect-electronic properties of {112} microfaceted surfaces of epitaxially grown CuInSe2 thin films are investigated by scanning tunneling spectroscopy and photoelectron spectroscopy techniques after various surface treatments. The intrinsic CuInSe2 surface is found to be largely passivated in terms of electronic defect levels in the band-gap region. However, surface oxidation leads to an overall high density of defect levels in conjunction with a considerable net surface dipole, which persists even after oxide removal. Yet, a subsequent annealing under vacuum restores the initial condition. Such oxidation/reduction cycles are reversible for many times providing robust control of the surface and interface properties in these materials. Based on ab initio simulations, a mechanism where oxygen dissociatively adsorbs and subsequently diffuses to a subsurface site is proposed as the initial step of the observed dipole formation. Our results emphasize the relevance of oxidation-induced dipole effects at the thin film surface and provide a comprehensive understanding toward passivation strategies of these surfaces.

In silico investigation of Cu(In,Ga)Se2-based solar cells - Mirhosseini, S. Hossein; Kormath Madam Raghupathy, Ramya; Sahoo, Sudhir K.; Wiebeler, Hendrik; Chugh, Manjusha; Kühne, Thomas (Phys. Chem. Chem. Phys.)
Photovoltaics is one of the most promising and fastest-growing renewable energy technologies. Although the price-performance ratio of solar cells has improved significantly over recent years{,} further systematic investigations are needed to achieve higher performance and lower cost for future solar cells. In conjunction with experiments{,} computer simulations are powerful tools to investigate the thermodynamics and kinetics of solar cells. Over the last few years{,} we have developed and employed advanced computational techniques to gain a better understanding of solar cells based on copper indium gallium selenide (Cu(In{,}Ga)Se2). Furthermore{,} we have utilized state-of-the-art data-driven science and machine learning for the development of photovoltaic materials. In this Perspective{,} we review our results along with a survey of the field.

A High-Rate Two-Dimensional Polyarylimide Covalent Organic Framework Anode for Aqueous Zn-Ion Energy Storage Devices - Yu, Minghao; Chandrasekhar, Naisa; Kormath Madam Raghupathy, Ramya; Ly, Khoa Hoang; Zhang, Haozhe; Dmitrieva, Evgenia; Liang, Chaolun; Lu, Xihong; Kühne, Thomas; Mirhosseini, S. Hossein; Weidinger, Inez M.; Feng, Xinliang (Journal of the American Chemical Society)
Rechargeable aqueous Zn-ion energy storage devices are promising candidates for next-generation energy storage technologies. However, the lack of highly reversible Zn2+-storage anode materials with low potential windows remains a primary concern. Here, we report a two-dimensional polyarylimide covalent organic framework (PI-COF) anode with high-kinetics Zn2+-storage capability. The well-organized pore channels of PI-COF allow the high accessibility of the build-in redox-active carbonyl groups and efficient ion diffusion with a low energy barrier. The constructed PI-COF anode exhibits a specific capacity (332 C g–1 or 92 mAh g–1 at 0.7 A g–1), a high rate capability (79.8% at 7 A g–1), and a long cycle life (85% over 4000 cycles). In situ Raman investigation and first-principle calculations clarify the two-step Zn2+-storage mechanism, in which imide carbonyl groups reversibly form negatively charged enolates. Dendrite-free full Zn-ion devices are fabricated by coupling PI-COF anodes with MnO2 cathodes, delivering excellent energy densities (23.9 ∼ 66.5 Wh kg–1) and supercapacitor-level power densities (133 ∼ 4782 W kg–1). This study demonstrates the feasibility of covalent organic framework as Zn2+-storage anodes and shows a promising prospect for constructing reliable aqueous energy storage devices.

Vibrational dynamics in lead halide hybrid perovskites investigated by Raman spectroscopy - Ibaceta-Jaña, Josefa; Muydinov, Ruslan; Rosado, Pamela; Mirhosseini, Hossein; Chugh, Manjusha; Nazarenko, Olga; Dirin, Dmitry N.; Heinrich, Dirk; Wagner, Markus R.; Kühne, Thomas; Szyszka, Bernd; Kovalenko, Maksym V.; et al. (Phys. Chem. Chem. Phys.)
Lead halide perovskite semiconductors providing record efficiencies of solar cells have usually mixed compositions doped in A- and X-sites to enhance the phase stability. The cubic form of formamidinium (FA) lead iodide reveals excellent opto-electronic properties but transforms at room temperature (RT) into a hexagonal structure which does not effectively absorb visible light. This metastable form and the mechanism of its stabilization by Cs+ and Br− incorporation are poorly characterized and insufficiently understood. We report here the vibrational properties of cubic FAPbI3 investigated by DFT calculations on phonon frequencies and intensities, and micro-Raman spectroscopy. The effects of Cs+ and Br− partial substitution are discussed. We support our results with the study of FAPbBr3 which expands the identification of vibrational modes to the previously unpublished low frequency region (<500 cm−1). Our results show that the incorporation of Cs+ and Br− leads to the coupling of the displacement of the A-site components and weakens the bonds between FA+ and the PbX6 octahedra. We suggest that the enhancement of α-FAPbI3 stability can be a product of the release of tensile stresses in the Pb–X bond, which is reflected in a red-shift of the low frequency region of the Raman spectrum (<200 cm−1).

Revealing the origin of the beneficial effect of cesium in highly efficient Cu(In,Ga)Se2 solar cells - Schöppe, Philipp; Schönherr, Sven; Chugh, Manjusha; Mirhosseini, Hossein; Jackson, Philip; Wuerz, Roland; Ritzer, Maurizio; Johannes, Andreas; Martínez-Criado, Gema; Wisniewski, Wolfgang; Schwarz, Torsten; T. Plass, Christian; et al. (Nano Energy)
The record conversion efficiency of thin-film solar cells based on Cu(In,Ga)Se2 (CIGS) absorbers has exceeded 23%. Such a high performance is currently only attainable by the incorporation of heavy alkali metals like Cs into the absorber through an alkali fluoride post-deposition treatment (PDT). As the effect of the incorporated heavy alkali metals is under discussion, we investigated the local composition and microstructure of high efficiency CIGS solar cells via various high-resolution techniques in a combinatory approach. An accumulation of Cs is clearly detected at the p-n junction along with variations in the local CIGS composition, showing the formation of a beneficial secondary phase with a laterally inhomogeneous distribution. Additionally, Cs accumulations were detected at grain boundaries with a random misorientation of the adjacent grains where a reduced Cu concentration and increased In and Se concentrations are detected. No accumulation was found at Σ3 twin boundaries as well as the grain interior. These experimental findings are in excellent agreement with complementary ab-initio calculations, demonstrating that the grain boundaries are passivated by the presence of Cs. Further, it is unlikely that Cs with its large ionic radius is incorporated into the CIGS grains where it would cause detrimental defects.

Effects of KF and RbF treatments on Cu(In,Ga)Se2-based solar cells: A combined photoelectron spectroscopy and DFT study - Majumdar, I.; Sahoo, S.K.; Parvan, V.; Mirhosseini, Hossein; Chacko, B.; Wang, Y.; Greiner, D.; Kühne, Thomas; Schlatmann, R.; Lauermann, I. (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Guanine condensates as covalent materials and the concept of cryptopores - Kossmann, Janina; Piankova, Diana; Tarakina, Nadezda V.; Heske, Julian Joachim; Kühne, Thomas; Schmidt, Johannes; Antonietti, Markus; López-Salas, Nieves (Carbon)
Keywords: General Chemistry; General Materials Science

Exploring Non-Equilibrium Molecular Dynamics of Mobile Protons in the Solid Acid CsH2PO4 on the Micrometer and Microsecond Scale - Dreßler, C.; Kabbe, G.; Brehm, Martin; Sebastiani, D. (J. Chem. Phys.)

Dissolving Cellulose in 1,2,3-Triazolium- and Imidazolium-Based Ionic Liquids with Aromatic Anions - Brehm, Martin; Radicke, J.; Pulst, M.; Shaabani, F.; Sebastiani, D.; Kressler, J. (Molecules)

Characterization of Aqueous Lower Polarity Solvation Shells Around Amphiphilic TEMPO Radicals in Water - Hunold, J.; Eisermann, J.; Brehm, Martin; Hinderberger, D. (J. Phys. Chem. B)

From Flat to Tilted: Gradual Interfaces in Organic Thin Film Growth - Scarbath-Evers, L.; Hammer, R.; Golze, D.; Brehm, Martin; Sebastiani, D.; Widdra, W. (Nanoscale)

Dynamical Matrix Propagator Scheme for Large-Scale Proton Dynamics Simulations - Dreßler, C.; Kabbe, G.; Brehm, Martin; Sebastiani, D. (J. Chem. Phys.)

Exploring Free Energy Profiles of Enantioselective Organocatalytic Aldol Reactions under Full Solvent Influence - Weiß, M.; Brehm, Martin (Molecules)

TRAVIS – A Free Analyzer for Trajectories from Molecular Simulation - Brehm, Martin; Thomas, M.; Gehrke, S.; Kirchner, B. (J. Chem. Phys.)

CP2K: An electronic structure and molecular dynamics software package - Quickstep: Efficient and accurate electronic structure calculations - Kühne, Thomas; Iannuzzi, Marcella; Ben, Mauro Del; Rybkin, Vladimir V.; Seewald, Patrick; Stein, Frederick; Laino, Teodoro; Khaliullin, Rustam Z.; Schütt, Ole; Schiffmann, Florian; Golze, Dorothea; Wilhelm, Jan; et al. (The Journal of Chemical Physics)
CP2K is an open source electronic structure and molecular dynamics software package to perform atomistic simulations of solid-state, liquid, molecular, and biological systems. It is especially aimed at massively parallel and linear-scaling electronic structure methods and state-of-theart ab initio molecular dynamics simulations. Excellent performance for electronic structure calculations is achieved using novel algorithms implemented for modern high-performance computing systems. This review revisits the main capabilities of CP2K to perform efficient and accurate electronic structure simulations. The emphasis is put on density functional theory and multiple post–Hartree–Fock methods using the Gaussian and plane wave approach and its augmented all-electron extension.

A Submatrix-Based Method for Approximate Matrix Function Evaluation in the Quantum Chemistry Code CP2K - Lass, Michael; Schade, Robert; Kühne, Thomas; Plessl, Christian (Proc. International Conference for High Performance Computing, Networking, Storage and Analysis (SC))
Electronic structure calculations based on density-functional theory (DFT) represent a significant part of today's HPC workloads and pose high demands on high-performance computing resources. To perform these quantum-mechanical DFT calculations on complex large-scale systems, so-called linear scaling methods instead of conventional cubic scaling methods are required. In this work, we take up the idea of the submatrix method and apply it to the DFT computations in the software package CP2K. For that purpose, we transform the underlying numeric operations on distributed, large, sparse matrices into computations on local, much smaller and nearly dense matrices. This allows us to exploit the full floating-point performance of modern CPUs and to make use of dedicated accelerator hardware, where performance has been limited by memory bandwidth before. We demonstrate both functionality and performance of our implementation and show how it can be accelerated with GPUs and FPGAs.

Accurate Sampling with Noisy Forces from Approximate Computing - Rengaraj, Varadarajan; Lass, Michael; Plessl, Christian; Kühne, Thomas (Computation)
In scientific computing, the acceleration of atomistic computer simulations by means of custom hardware is finding ever-growing application. A major limitation, however, is that the high efficiency in terms of performance and low power consumption entails the massive usage of low precision computing units. Here, based on the approximate computing paradigm, we present an algorithmic method to compensate for numerical inaccuracies due to low accuracy arithmetic operations rigorously, yet still obtaining exact expectation values using a properly modified Langevin-type equation.

Accessing the Accuracy of Density Functional Theory through Structure and Dynamics of the Water–Air Interface - Ohto, Tatsuhiko; Dodia, Mayank; Xu, Jianhang; Imoto, Sho; Tang, Fujie; Zysk, Frederik; Kühne, Thomas D.; Shigeta, Yasuteru; Bonn, Mischa; Wu, Xifan; Nagata, Yuki (The Journal of Physical Chemistry Letters)

Unconventional phase III of high-pressure solid hydrogen - Azadi, Sam; Kühne, Thomas D. (Physical Review B)

Vibrational Properties of RbInSe2: Raman Scattering Spectroscopy and First-Principle Calculations - Guc, Maxim; Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Mirhosseini, Hossein; Kühne, Thomas D.; Becerril-Romero, Ignacio; Pérez-Rodríguez, Alejandro; Kaufmann, Christian A.; Izquierdo-Roca, Victor (The Journal of Physical Chemistry C)

Experimental and Theoretical High Energy Resolution Hard X-ray Absorption and Emission Spectroscopy on Biomimetic Cu2S2 Complexes - Müller, Patrick; Neuba, Adam; Flörke, Ulrich; Henkel, Gerald; Kühne, Thomas D.; Bauer, Matthias (The Journal of Physical Chemistry A)

Experimental and theoretical (high energy resolution) X-ray absorption and emission spectroscopy / vorgelegt von Patrick Müller ; [Promotionskommission: Prof. Dr.-Ing. Hans-Joachim Warnecke, Vorsitz; Prof. Dr. Matthias Bauer, Erstgutachter; Prof. Dr. Thomas D. Kühne, Zweitgutachter; Prof. Dr. Wolf Gero Schmidt] - Müller, Patrick

Properties of Co-Evaporated RbInSe2 Thin Films - Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Bertram, Tobias; Maticiuc, Natalia; Yetkin, Hasan A; Gunder, René; Schlatmann, Rutger; Kühne, Thomas D; Kaufmann, Christian A; Mirhosseini, Hossein (physica status solidi (RRL)--Rapid Research Letters)

Opposing Electronic and Nuclear Quantum Effects on Hydrogen Bonds in H2O and D2O - Clark, Timothy; Heske, Julian Joachim; Kühne, Thomas (ChemPhysChem)
Abstract The effect of extending the O−H bond length(s) in water on the hydrogen-bonding strength has been investigated using static ab initio molecular orbital calculations. The “polar flattening” effect that causes a slight σ-hole to form on hydrogen atoms is strengthened when the bond is stretched, so that the σ-hole becomes more positive and hydrogen bonding stronger. In opposition to this electronic effect, path-integral ab initio molecular-dynamics simulations show that the nuclear quantum effect weakens the hydrogen bond in the water dimer. Thus, static electronic effects strengthen the hydrogen bond in H2O relative to D2O, whereas nuclear quantum effects weaken it. These quantum fluctuations are stronger for the water dimer than in bulk water.
Keywords: ab initio calculations; bond theory; hydrogen bonds; isotope effects; solvent effects

Impact of intermolecular vibrational coupling effects on the sum-frequency generation spectra of the water/air interface - Kaliannan, Naveen Kumar; Henao Aristizabal, Andres; Wiebeler, Hendrik; Zysk, Frederik; Ohto, Tatsuhiko; Nagata, Yuki; D. Kühne, Thomas (Molecular Physics)

Experimental and Theoretical High Energy Resolution Hard X-ray Absorption and Emission Spectroscopy on Biomimetic Cu2S2 Complexes - Müller, Patrick; Neuba, Adam; Flörke, Ulrich; Henkel, Gerald; Kühne, Thomas D.; Bauer, Matthias (The Journal of Physical Chemistry A)

Controlling the strength of interaction between carbon dioxide and nitrogen-rich carbon materials by molecular design - Walczak, Ralf; Savateev, Aleksandr; Heske, Julian Joachim; Tarakina, Nadezda V.; Sahoo, Sudhir; Epping, Jan D.; Kühne, Thomas; Kurpil, Bogdan; Antonietti, Markus; Oschatz, Martin (Sustainable Energy Fuels)
Thermal treatment of hexaazatriphenylene-hexacarbonitrile (HAT-CN) in the temperature range from 500 °C to 700 °C leads to precise control over the degree of condensation{,} and thus atomic construction and porosity of the resulting C2N-type materials. Depending on the condensation temperature of HAT-CN{,} nitrogen contents of more than 30 at% can be reached. In general{,} these carbons show adsorption properties which are comparable to those known for zeolites but their pore size can be adjusted over a wider range. At condensation temperatures of 525 °C and below{,} the uptake of nitrogen gas remains negligible due to size exclusion{,} but the internal pores are large and polarizing enough that CO2 can still adsorb on part of the internal surface. This leads to surprisingly high CO2 adsorption capacities and isosteric heat of adsorption of up to 52 kJ mol−1. Theoretical calculations show that this high binding enthalpy arises from collective stabilization effects from the nitrogen atoms in the C2N layers surrounding the carbon atom in the CO2 molecule and from the electron acceptor properties of the carbon atoms from C2N which are in close proximity to the oxygen atoms in CO2. A true CO2 molecular sieving effect is achieved for the first time in such a metal-free organic material with zeolite-like properties{,} showing an IAST CO2/N2 selectivity of up to 121 at 298 K and a N2/CO2 ratio of 90/10 without notable changes in the CO2 adsorption properities over 80 cycles.

Enhancement of the asymmetry in the hydrogen bond network of liquid water by an ultrafast electric field pulse - Elgabarty, Hossam; Kaliannan, Naveen Kumar; Kühne, Thomas D. (Scientific Reports)

Diffusion of Alkali Metals in Polycrystalline CuInSe2 and Their Role in the Passivation of Grain Boundaries - Chugh, Manjusha; Kühne, Thomas D.; Mirhosseini, Hossein (ACS Applied Materials & Interfaces)
The behavior of alkali atom point defects in polycrystalline CuInSe2 is studied. In this work, three grain boundary models, one coherent twin boundary and two twin boundaries with dislocation cores, are considered. Total energy calculations show that all alkali metals tend to segregate at the grain boundaries. In addition, the segregation of alkali atoms is more pronounced at the grain boundaries with the dislocation cores. The diffusion of alkali metals along and near grain boundaries is studied as well. The results show that the diffusion of alkali atoms in the grain boundary models is faster than within the bulk. In addition, the ion exchange between Na and Rb atoms at the grain boundaries leads to the Rb enrichment at the grain boundaries and the increase of the Na concentration in the bulk. While the effects of Na and Rb point defects on the electronic structure of the grain boundary with the anion-core dislocation are similar, Rb atoms passivate the grain boundary with the cation-core dislocation more effectively than Na. This can explain the further improvement of the solar cell performance after the RbF-postdeposition treatment.

Computing Bulk Phase Resonance Raman Spectra from ab initio Molecular Dynamics and Real-Time TDDFT - Brehm, Martin; Thomas, M. (J. Chem. Theory Comput.)

Triazolium-Based Ionic Liquids – A Novel Class of Cellulose Solvents - Brehm, Martin; Pulst, M.; Kressler, J.; Sebastiani, D. (J. Phys. Chem. B)

A General Algorithm to Calculate the Inverse Principal p-th Root of Symmetric Positive Definite Matrices - Richters, Dorothee; Lass, Michael; Walther, Andrea; Plessl, Christian; Kühne, Thomas (Communications in Computational Physics)
We address the general mathematical problem of computing the inverse p-th root of a given matrix in an efficient way. A new method to construct iteration functions that allow calculating arbitrary p-th roots and their inverses of symmetric positive definite matrices is presented. We show that the order of convergence is at least quadratic and that adaptively adjusting a parameter q always leads to an even faster convergence. In this way, a better performance than with previously known iteration schemes is achieved. The efficiency of the iterative functions is demonstrated for various matrices with different densities, condition numbers and spectral radii.

Using Approximate Computing for the Calculation of Inverse Matrix p-th Roots - Lass, Michael; Kühne, Thomas; Plessl, Christian (Embedded Systems Letters)
Approximate computing has shown to provide new ways to improve performance and power consumption of error-resilient applications. While many of these applications can be found in image processing, data classification or machine learning, we demonstrate its suitability to a problem from scientific computing. Utilizing the self-correcting behavior of iterative algorithms, we show that approximate computing can be applied to the calculation of inverse matrix p-th roots which are required in many applications in scientific computing. Results show great opportunities to reduce the computational effort and bandwidth required for the execution of the discussed algorithm, especially when targeting special accelerator hardware.

Theoretical Investigation of Interaction of CuInSe2 Absorber Material with Oxygen, Hydrogen, and Water - Sahoo, Sudhir; Kormath Madam Raghupathy, Ramya; Kühne, Thomas; Mirhosseini, Hossein (J. Phys. Chem. C)
We performed ab initio calculations to study oxygen and hydrogen point defects in the CuInSe2 (CISe) solar-cell material. We found that H interstitial defects (when one H atom is surrounded by four Se atoms) and HCu (when a H atom is replacing a Cu atom) are the most stable defects. Whereas these H substitutional defects remain neutral, H interstitial defects act as donor defects and are detrimental to the cell performance. The incorporation of H2 into the CISe lattice, on the other hand, is harmless to the p-type conductivity. Oxygen atoms tend to either substitute Se atoms in the CISe lattice or form interstitial defects, though the formation of substitutional defects is more favorable. All oxygen point defects have high formation energies, which results in a low concentration of these defects in CISe. However, the presence of oxygen in the system leads to the formation of secondary phases such as In2O3 and InCuO2. In addition to the point defects, we studied the adsorption of H2O molecules on a defect-free surface and a surface with a (2VCu + InCu) defect using the ab initio thermodynamics technique. Our results indicate that the dissociative water adsorption on the CISe surface is energetically unfavorable. Furthermore, in order to obtain a water-free surface, the surface with defects has to be calcined at a higher temperature compared to the defect-free surface.

Database screening of ternary chalcogenides for p-type transparent conductors - Kormath Madam Raghupathy, Ramya; Wiebeler, Hendrik; Kühne, Thomas; Felser, Claudia; Mirhosseini, Hossein (Chemistry of Materials)
In this work, we investigated ternary chalcogenide semiconductors to identify promising p-type transparent conducting materials (TCMs). High-throughput calculations were employed to find the compounds that satisfies our screening criteria. Our screening strategy was based on the size of band gaps, the values of hole effective masses, and p-type dopability. Our search led to the identification of seven promising compounds (IrSbS, Ba2GeSe4, Ba2SiSe4, Ba(BSe3)2, VCu3S4, NbCu3Se4, and CuBS2) as potential TCM candidates. In addition, branch point energy and optical absorption spectra calculations support our findings. Our results open a new direction for the design and development of p-type TCMs.

Impact of finite-temperature and condensed-phase effects on theoretical X-ray absorption spectra of transition metal complexes - Müller, Patrick; Karhan, Kristof; Krack, Matthias; Gerstmann, Uwe; Schmidt, Wolf Gero; Bauer, Matthias; Kühne, Thomas D. (Journal of Computational Chemistry)

Nanoscopic Structures and Molecular Interactions Leading to a Dystectic and two Eutectic Points in [EMIm][Cl] / Urea Mixtures - Cerajewski, U.; Träger, J.; Henkel, S.; Roos, A. H.; Brehm, Martin; Hinderberger, D. (Phys. Chem. Chem. Phys.)

Structure and Lifetimes in Ionic Liquids and their Mixtures - Gehrke, S.; von Domaros, M.; Clark, R.; Hollóczki, O.; Brehm, Martin; Welton, T.; Luzar, A.; Kirchner, B. (Faraday Discuss.)

Salt Bridge in Aqueous Solution: Strong Structural Motifs but Weak Enthalpic Effects - Pylaeva, S.; Brehm, Martin; Sebastiani, D. (Sci. Rep.)

An Efficient Lossless Compression Algorithm for Trajectories of Atom Positions and Volumetric Data - Brehm, Martin; Thomas, M. (J. Chem. Inf. Model.)

Simulating Structure and Dynamics in Small Droplets of 1-Ethyl-3-Methylimidazolium Acetate - Brehm, Martin; Sebastiani, D. (J. Chem. Phys.)

A Massively Parallel Algorithm for the Approximate Calculation of Inverse p-th Roots of Large Sparse Matrices - Lass, Michael; Mohr, Stephan; Wiebeler, Hendrik; Kühne, Thomas; Plessl, Christian (Proc. Platform for Advanced Scientific Computing (PASC) Conference)
We present the submatrix method, a highly parallelizable method for the approximate calculation of inverse p-th roots of large sparse symmetric matrices which are required in different scientific applications. Following the idea of Approximate Computing, we allow imprecision in the final result in order to utilize the sparsity of the input matrix and to allow massively parallel execution. For an n x n matrix, the proposed algorithm allows to distribute the calculations over n nodes with only little communication overhead. The result matrix exhibits the same sparsity pattern as the input matrix, allowing for efficient reuse of allocated data structures. We evaluate the algorithm with respect to the error that it introduces into calculated results, as well as its performance and scalability. We demonstrate that the error is relatively limited for well-conditioned matrices and that results are still valuable for error-resilient applications like preconditioning even for ill-conditioned matrices. We discuss the execution time and scaling of the algorithm on a theoretical level and present a distributed implementation of the algorithm using MPI and OpenMP. We demonstrate the scalability of this implementation by running it on a high-performance compute cluster comprised of 1024 CPU cores, showing a speedup of 665x compared to single-threaded execution.
Keywords: approximate computing; linear algebra; matrix inversion; matrix p-th roots; numeric algorithm; parallel computing

Efficient PAW-based bond strength analysis for understanding the In/Si(111)(8 × 2) – (4 × 1) phase transition - Lücke, Andreas; Gerstmann, Uwe; Kühne, Thomas D.; Schmidt, Wolf G. (Journal of Computational Chemistry)
A numerically efficient yet highly accurate implementation of the crystal orbital Hamilton population (COHP) scheme for plane-wave calculations is presented. It is based on the projector-augmented wave (PAW) formalism in combination with norm-conserving pseudopotentials and allows to extract chemical interactions between atoms from band-structure calculations even for large and complex systems. The potential of the present COHP implementation is demonstrated by an in-depth analysis of the intensively investigated metal-insulator transition in atomic-scale indium wires self-assembled on the Si(111) surface. Thereby bond formation between In atoms of adjacent zigzag chains is found to be instrumental for the phase change. © 2017 Wiley Periodicals, Inc.
Keywords: density functional theory; bonding; crystal orbital Hamilton population; indium nanowires; phase transition

High-pressure hydrogen sulfide by diffusion quantum Monte Carlo - Azadi, Sam; Kühne, Thomas D. (The Journal of Chemical Physics)

Efficient PAW-based bond strength analysis for understanding the In/Si(111)(8 × 2) - (4 × 1) phase transition - Lücke, Andreas; Gerstmann, Uwe; Kühne, Thomas D.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Influence of Small Fluorophilic and Lipophilic Organic Molecules on Dipalmitoylphosphatidylcholine Bilayers - Brehm, Martin; Saddiq, G.; Watermann, T.; Sebastiani, D. (J. Phys. Chem. B)

Computing Bulk Phase Raman Optical Activity Spectra from ab initio Molecular Dynamics Simulations - Brehm, Martin; Thomas, M. (J. Phys. Chem. Lett.)

Glutathione Adduct Patterns of Michael-Acceptor Carbonyls - Slawik, C.; Rickmeyer, C.; Brehm, Martin; Böhme, A.; Schüürmann, G. (Environ. Sci. Technol.)

An Integrated Data-Driven Strategy for Safe-by-Design Nanoparticles: The FP7 MODERN Project. - Brehm, Martin; Kafka, A.; Bamler, M.; Kühne, R.; Schüürmann, G.; Sikk, L.; Burk, J.; Burk, P.; Tamm, T.; Tämm, K.; Pokhrel, S.; Mädler, L.; et al. (Adv. Exp. Med. Biol.)

Polyphilic Interactions as Structural Driving Force Investigated by Molecular Dynamics Simulation (Project 7) - Peschel, Christopher; Brehm, Martin; Sebastiani, Daniel (Polymers)
We investigated the effect of fluorinated molecules on dipalmitoylphosphatidylcholine (DPPC) bilayers by force-field molecular dynamics simulations. In the first step, we developed all-atom force-field parameters for additive molecules in membranes to enable an accurate description of those systems. On the basis of this force field, we performed extensive simulations of various bilayer systems containing different additives. The additive molecules were chosen to be of different size and shape, and they included small molecules such as perfluorinated alcohols, but also more complex molecules. From these simulations, we investigated the structural and dynamic effects of the additives on the membrane properties, as well as the behavior of the additive molecules themselves. Our results are in good agreement with other theoretical and experimental studies, and they contribute to a microscopic understanding of interactions, which might be used to specifically tune membrane properties by additives in the future.
Keywords: Polymers and Plastics; General Chemistry

N-Heterocyclic Carbene Complexes of Iron as Photosensitizers for Light-Induced Water Reduction - Zimmer, Peter; Müller, Patrick; Burkhardt, Lukas; Schepper, Rahel; Neuba, Adam; Steube, Jakob; Dietrich, Fabian; Flörke, Ulrich; Mangold, Stefan; Gerhards, Markus; Bauer, Matthias (European Journal of Inorganic Chemistry)

Atomic and electronic structures evolution of the narrow band gap semiconductor Ag2Se under high pressure - Naumov, P; Barkalov, O; Mirhosseini, Hossein; Felser, C; A Medvedev, S (Journal of Physics: Condensed Matter)
Non-trivial electronic properties of silver telluride and other chalcogenides, such as the presence of a topological insulator state, electronic topological transitions, metallization, and the possible emergence of superconductivity under pressure have attracted attention in recent years. In this work, we studied the electronic properties of silver selenide (Ag2Se). We performed direct current electrical resistivity measurements, in situ Raman spectroscopy, and synchrotron x-ray diffraction accompanied by ab initio calculations to explore pressure-induced changes to the atomic and electronic structure of Ag2Se. The temperature dependence of the electrical resistivity was measured up to 30 GPa in the 4–300 K temperature interval. Resistivity data showed an unusual increase in the thermal energy gap of phase I, which is a semiconductor under ambient conditions. Recently, a similar effect was reported for the 3D topological insulator Bi2Se3. Raman spectroscopy studies revealed lattice instability in phase I indicated by the softening of observed vibrational modes with pressure. Our hybrid functional band structure calculations predicted that phase I of Ag2Se would be a narrow band gap semiconductor, in accordance with experimental results. At a pressure of ~7.5 GPa, Ag2Se underwent a structural transition to phase II with an orthorhombic Pnma structure. The temperature dependence of the resistivity of Ag2Se phase II demonstrated its metallic character. Ag2Se phase III, which is stable above 16.5 GPa, is also metallic according to the resistivity data. No indication of the superconducting transition is found above 4 K in the studied pressure range.

Improved parameterization of the quantum harmonic oscillator model based on localized wannier functions to describe Van der Waals interactions in density functional theory - Partovi-Azar, Pouya; Berg, Matthias; Sanna, Simone; Kühne, Thomas D. (International Journal of Quantum Chemistry)
Recently, the quantum harmonic oscillator model has been combined with maximally localized Wannier functions to account for long-range dispersion interactions in density functional theory calculations (Silvestrelli, J. Chem. Phys. 2013, 139, 054106). Here, we present a new, improved set of values for the three parameters involved in this scheme. To test the new parameter set we have computed the potential energy curves for various systems, including an isolated Ar2 dimer, two N2 dimers interacting within different configurations, and a water molecule physisorbed on pristine graphene. While the original set of parameters generally overestimates the interaction energies and underestimates the equilibrium distances, the new parameterization substantially improves the agreement with experimental and theoretical reference values. © 2016 Wiley Periodicals, Inc.
Keywords: Wannier orbitals; Van der Waals interactions; density functional theory; quantum harmonic oscillator

Assessing the accuracy of improved force-matched water models derived from Ab initio molecular dynamics simulations - Köster, Andreas; Spura, Thomas; Rutkai, Gábor; Kessler, Jan; Wiebeler, Hendrik; Vrabec, Jadran; Kühne, Thomas D. (Journal of Computational Chemistry)
The accuracy of water models derived from ab initio molecular dynamics simulations by means on an improved force-matching scheme is assessed for various thermodynamic, transport, and structural properties. It is found that although the resulting force-matched water models are typically less accurate than fully empirical force fields in predicting thermodynamic properties, they are nevertheless much more accurate than generally appreciated in reproducing the structure of liquid water and in fact superseding most of the commonly used empirical water models. This development demonstrates the feasibility to routinely parametrize computationally efficient yet predictive potential energy functions based on accurate ab initio molecular dynamics simulations for a large variety of different systems. © 2016 Wiley Periodicals, Inc.
Keywords: liquid water; force matching; ab initio; molecular dynamics; Monte Carlo

Quantum ring-polymer contraction method: Including nuclear quantum effects at no additional computational cost in comparison to ab Initio molecular dynamics - John, Christopher; Spura, Thomas; Kühne, Thomas D. (Phys. Rev. E)

Using Approximate Computing in Scientific Codes - Lass, Michael; Kühne, Thomas; Plessl, Christian (Workshop on Approximate Computing (AC))

Anaerobic Microbial Transformation of Halogenated Aromatics and Fate Prediction Using Electron Density Modeling - Cooper, M.; Wagner, A.; Wondrousch, D.; Sonntag, F.; Sonnabend, A.; Brehm, Martin; Schüürmann, G.; Adrian, L. (Environ. Sci. Technol.)

Triphilic Ionic-Liquid Mixtures: Fluorinated and Non-Fluorinated Aprotic Ionic-Liquid Mixtures - Hollóczki, O.; Macchiagodena, M.; Weber, H.; Thomas, M.; Brehm, Martin; Stark, A.; Russina, O.; Triolo, A.; Kirchner, B. (ChemPhysChem)

Domain Analysis in Nanostructured Liquids: A Post-Molecular Dynamics Study at the Example of Ionic Liquids - Brehm, Martin; Weber, H.; Thomas, M.; Hollóczki, O.; Kirchner, B. (ChemPhysChem)

Voronoi Dipole Moments for the Simulation of Bulk Phase Vibrational Spectra - Thomas, M.; Brehm, Martin; Kirchner, B. (Phys. Chem. Chem. Phys.)

Covalency of hydrogen bonds in liquid water can be probed by proton nuclear magnetic resonance experiments - Elgabarty, Hossam; Khaliullin, Rustam Z.; Kühne, Thomas D. (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

A Theoretical and Experimental Chemist’s Joint View on Hydrogen Bonding in Ionic Liquids and Their Binary Mixtures - Stark, A.; Brehm, Martin; Brüssel, M.; Lehmann, S. B. C.; Pensado, A. S.; Schöppke, M.; Kirchner, B. (Top. Curr. Chem.)

Simulating the Vibrational Spectra of Ionic Liquid Systems: 1-Ethyl-3-Methylimidazolium Acetate and its Mixtures - Thomas, M.; Brehm, Martin; Hollóczki, O.; Kelemen, Z.; Nyulászi, L.; Pasinszki, T.; Kirchner, B. (J. Chem. Phys.)

Interactions in Ionic Liquids probed by in situ NMR Spectroscopy - Giernoth, R.; Bröhl, A.; Brehm, Martin; Lingscheid, Y. (J. Mol. Liq.)

Understanding Ionic Liquids from Theoretical Methods - Zahn, S.; Brehm, Martin; Brüssel, M.; Hollóczki, O.; Kohagen, M.; Lehmann, S. B. C.; Malberg, F.; Pensado, A. S.; Schöppke, M.; Weber, H.; Kirchner, B. (J. Mol. Liq.)

How Can a Carbene be Active in an Ionic Liquid? - Thomas, M.; Brehm, Martin; Hollóczki, O.; Kirchner, B. (Chem. Eur. J)

Sign problem of the fermionic shadow wave function - Calcavecchia, Francesco; Pederiva, Francesco; Kalos, Malvin H.; Kühne, Thomas D. (Phys. Rev. E)

Self-consistent field theory based molecular dynamics with linear system-size scaling - Richters, Dorothee (J. Chem. Phys.)

Liquid Structure and Cluster Formation in Ionic Liquid/Water Mixtures – An Extensive ab initio Molecular Dynamics Study on 1-Ethyl-3-Methylimidazolium Acetate/Water Mixtures – Part 2 - Brehm, Martin; Weber, H.; Pensado, A. S.; Stark, A.; Kirchner, B. (Z. Phys. Chem.)

Understanding the Evaporation of Ionic Liquids using the Example of 1-Ethyl-3-Methylimidazolium Ethylsulfate - Malberg, F.; Brehm, Martin; Hollóczki, O.; Pensado, A. S.; Kirchner, B. (Phys. Chem. Chem. Phys.)

Carbene Formation in Ionic Liquids: Spontaneous, Induced, or Prohibited? - Hollóczki, O.; Firaha, D. S.; Friedrich, J.; Brehm, Martin; Cybik, R.; Wild, M.; Stark, A.; Kirchner, B. (J. Phys. Chem. B)

Computing Vibrational Spectra from ab initio Molecular Dynamics - Thomas, M.; Brehm, Martin; Fligg, R.; Vöhringer, P.; Kirchner, B. (Phys. Chem. Chem. Phys.)

Electronic signature of the instantaneous asymmetry in the first coordination shell of liquid water - Kühne, Thomas D.; Khaliullin, Rustam Z. (Nature Commun.)

Effect of Dispersion on the Structure and Dynamics of the Ionic Liquid 1-Ethyl-3-Methylimidazolium Thiocyanate - Pensado, A. S.; Brehm, Martin; Thar, J.; Seitsonen, A. P.; Kirchner, B. (ChemPhysChem)

Short Time Dynamics of Ionic Liquids in AIMD-Based Power Spectra - Wendler, K.; Brehm, Martin; Malberg, F.; Kirchner, B.; Site, L. Delle (J. Chem. Theory Comput.)

A One-Parameter Quantum Cluster Equilibrium Approach - Brüssel, M.; Perlt, E.; von Domaros, M.; Brehm, Martin; Kirchner, B. (J. Chem. Phys.)

Proton Transfer and Polarity Changes in Ionic Liquid–Water Mixtures: A Perspective on Hydrogen Bonds from ab initio Molecular Dynamics at the Example of 1-Ethyl-3-Methylimidazolium Acetate–Water Mixtures—Part 1 - Brehm, Martin; Weber, H.; Pensado, A. S.; Stark, A.; Kirchner, B. (Phys. Chem. Chem. Phys.)

On the Ideality of Binary Mixtures of Ionic Liquids - Brüssel, M.; Brehm, Martin; Pensado, A. S.; Malberg, F.; Ramzan, M.; Stark, A.; Kirchner, B. (Phys. Chem. Chem. Phys.)

How Hydrogen Bonds Influence the Mobility of Imidazolium-Based Ionic Liquids. A Combined Theoretical and Experimental Study of 1-n-Butyl-3-Methylimidazolium Bromide - Kohagen, M.; Brehm, Martin; Lingscheid, Y.; Giernoth, R.; Sangoro, J.; Kremer, F.; Naumov, S.; Iacob, C.; Kärger, J.; Valiullin, R.; Kirchner, B. (J. Phys. Chem. B)

Performance of Quantum Chemically Derived Charges and Persistence of Ion Cages in Ionic Liquids. A Molecular Dynamics Simulations Study of 1-n-Butyl-3-Methylimidazolium Bromide - Kohagen, M.; Brehm, Martin; Thar, J.; Zhao, W.; Müller-Plathe, F.; Kirchner, B. (J. Phys. Chem. B)